PLATINUM METAL MINERALIZATION OF THE SOUTH URALS MAGMATIC COMPLEXES: GEOLOGICAL AND GEODYNAMIC CHARACTERISTICS OF FORMATIONS, PROBLEMS OF THEIR GENESIS, AND PROSPECTS - I. R. Rakhimov; D. E. Saveliev; A. V. Vishnevskiy (Геодинамика и тектонофизика, 2021)
In the South Urals, we have identified and investigated two platinum-bearing formations – ophiolite chromitebearing complexes, and the Khudolaz differentiated mafic-ultramafic complex with sulfide Cu-Ni mineralization. The ophiolite chromite-bearing complexes include fragments of the upper mantle and lower crust of the Paleouralian Ocean, which were induced by collision onto the edge of the East European platform. The origin of the Khudolaz complex is related a mantle plume activity. Here, we review and compare the main features of platinum-metal mineralization (PMM) in these two formations.The article presents the results of mineralogical and geochemical studies of PMM associated with chromite and sulfide Cu-Ni ores. In association with chromitites, two types of PMM are distinguished: (1) predominating refractory platinoids in chromitites of the mantle unit of the section, and (2) predominating platinum and palladium in chromitites of the transitional wehrlite-clinopyroxenite complex. Compositions of platinum group minerals (PGM) and relations between their elements and host minerals suggest that the minerals of the ophiolite chromite-bearing complexes are of a restite origin, while the Khudolaz complex results from a combination of magmatic processes and solid-phase redistribution of material. Palladium (michenerite, froodite, merenskyite, borovskite, sudburyite) and platinum (sperrylite, moncheite) minerals are found in magmatic sulfide ores of the Khudolaz complex, which were subjected to hydrothermal metasomatization. Texture observations using electron microscope and optical (reflected light) images, as well as LA ICP MS analyses of sulfides suggest late- and post-magmatic crystallization of PMM in three phases: (1) immiscible metalloid or highly fractionated residual sulfide melts trapped in sulfides; (2) segregation of isomorphic impurities of platinum group elements (PGE) and chalcogenide elements from sulfide solid solutions; and (3) interaction of hydrothermal fluids with soluble sulfides.Prospective for PMM are extended bodies of disseminated chromitites in marginal dunites of the Kraka and Nurali massifs, and wehrlite-clinopyroxenite complexes of the same massifs containing PGE (above 500 ppb). In the Khudolaz complex, promising PMM bodies are low-metasomatized parts of sulfide ore bodies (1 ppm of ΣPGE and above) located in the largest massifs, Severny Buskun and Zapadny Karasaz. Exocontact zones of these intrusions are also promising for PMM.